2017
DOI: 10.1108/jocm-03-2016-0053
|View full text |Cite
|
Sign up to set email alerts
|

Strategic patterns and firm performance: comparing consistent, flexible and reactor strategies

Abstract: Purpose Firms face the paradox of adapting change and remaining stable to control uncertainty simultaneously to maintain their competitive position because both aspects are essential for the firm’s effectiveness. This has raised a debate in the contemporary literature that whether firms should remain consistent or adapt flexibility in their strategic choice to produce better performance? The supporters of both the arguments provide substantial evidence in their favor. The purpose of this paper is to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 37 publications
0
17
0
4
Order By: Relevance
“…Inspired by the contingency theoretical perspective on organizations (e.g. Anwar and Hasnu, 2017;Moss et al, 2014;Huber, 2011, Donaldson, 2001Burton et al, 2015), the current study adopted firm size, strategic clarity, industry, whether the company is a multi-/single plant firm, exporter status, business environment risk and level of industrial competition as contingency factors. The study then tested the impact of these factors on the mediating effects, as previous studies indicated that they might have a bearing on those variables and relationships (e.g.…”
Section: Contingency Factorsmentioning
confidence: 99%
“…Inspired by the contingency theoretical perspective on organizations (e.g. Anwar and Hasnu, 2017;Moss et al, 2014;Huber, 2011, Donaldson, 2001Burton et al, 2015), the current study adopted firm size, strategic clarity, industry, whether the company is a multi-/single plant firm, exporter status, business environment risk and level of industrial competition as contingency factors. The study then tested the impact of these factors on the mediating effects, as previous studies indicated that they might have a bearing on those variables and relationships (e.g.…”
Section: Contingency Factorsmentioning
confidence: 99%
“…The evidence that has been released is highly contradictory. According to Anwar and Hasnu (2017) firms' external relations moderate more by the specific industry then by the firm size. Kalkan et al (2011) and Campos-Climent and Sanchis-Palacio (2015), carrying out their research in different contexts, found that there is no relation between size and firm performance including any innovation activity.…”
Section: Firm Size and Organizational Innovation Typesmentioning
confidence: 99%
“…The review is based on: “Strategic patterns and firm performance: comparing consistent, flexible and reactor strategies” by Anwar and Hasnu (2017), published in Journal of Organizational Change Management . Choice of strategy can significantly impact on organizational performance.…”
Section: Commentmentioning
confidence: 99%